FACTORS AFFECTING THE AUCTION LIMIT VALUE OF NON PERFORMING LOANS COLLATERAL AT PT. BANK NEGARA INDONESIA (PERSERO), TBK. PAPUA REGION - Andiyamin Andiyamin; Elisabet Siahaan; Handy Octavianus (Adisam Publisher, 2025)
This study aims to analyse the factors that influence the auction limit value of non-performing loans at PT. Bank Negara Indonesia (Persero), Tbk. Papua Region. The independent variables analysed include exposure time, collateral location, collateral condition, market value, and liquidation value. Data were collected from internal auction documents and analysed using multiple linear regression. The results show that exposure time has a negative and significant effect on auction limit value, meaning that the longer the property remains unsold and goes through repeated auctions, the more its limit value tends to decrease. The location of the collateral showed a positive effect on the limit value, but it was not significant at the 95% confidence level. The condition of the collateral had a positive and significant effect on the limit value, indicating that properties in better condition had higher limit values. Market value also had a positive and significant effect on the limit value, reinforcing the role of market value as the basis for determining the auction limit value. Conversely, the liquidation value has a negative and significant effect on the limit value, indicating that the higher the liquidation value of collateral, the lower the limit value tends to be compared to its market value. Among the independent variables analysed, the condition of the collateral has the most significant effect. This confirms that collateral conditions in the form of structurally safe and well-maintained property, with complete legality and located in a strategic environment, will reduce the risk of value decline and open up opportunities to obtain auction prices with the highest limit value. These findings are expected to provide strategic information for banks in setting more accurate and effective auction limit values.